Strategi Pengumpulan Zakat, Infak, dan Sedekah ASN Muslim di Daerah Minoritas - Salma Saharuddin; Jamaluddin Jamaluddin; Syawaluddin Syawaluddin (Universitas Islam Darud Da'wah Wal-Irsyad A.G.H. Abdurrahman Ambo Dalle, 2025)
This study examines the strategies for collecting zakat, infaq, and sadaqah (ZIS) from Muslim civil servants (ASN) in minority Muslim areas, focusing on a case study of BAZNAS Mamasa Regency. The research employs a qualitative approach with a field research design to explore collection strategies, challenges, and supporting factors within a socio-cultural minority context. Data were collected through in-depth interviews, field observations, and document analysis involving BAZNAS administrators and Muslim ASN. The findings reveal that ZIS collection strategies in Mamasa are not implemented through a payroll deduction system but rely on persuasive-educative, institutional, and cultural approaches. These strategies emphasize voluntary participation, religious awareness, tolerance, and inclusive communication to maintain social harmony in a predominantly non-Muslim environment. The study also identifies several challenges, including the limited number of Muslim ASN, social sensitivity, and varying levels of understanding regarding professional zakat. Nevertheless, supporting factors such as religious awareness, the role of religious counselors, and public trust in BAZNAS contribute significantly to the sustainability of ZIS collection.